Preventive and Curative Care Utilization Among Mexican Immigrant Women in Birmingham, AL (2012)
ABSTRACT: his study aims to describe the utilization of curative and preventive care among Mexican immigrant women in the country of origin versus the US, and to identify factors associated with preventive and curative care utilization. A cross-sectional sample of 185 Mexican immigrant women living in Birmingham, AL between 2004 and 2005 were included in this study. Fisher’s Exact tests showed that there was a statistically significant difference between seeking curative care (p < 0.0001) and preventive care (p < 0.0001) in country of origin versus the US. Differences in the reasons for lack of utilization of both curative and preventive care were also observed in the US and the country of origin. These findings suggest that difference in healthcare-seeking behaviors and utilization among Mexican immigrant women between the US and their country of origin may be useful in the development of interventions aimed at increasing the use of preventive and curative care services to this immigrant population in the US.